Chloride nutrition improves drought resistance by enhancing water deficit avoidance and tolerance mechanisms. (30th March 2021) - Franco-Navarro, Juan D; Díaz-Rueda, Pablo; Rivero-Núñez, Carlos M; Brumós, Javier; Rubio-Casal, Alfredo E; de Cires, Alfonso; Colmenero-Flores, José M; Rosales, Miguel A
Abstract : Chloride nutrition at macronutrient levels reduces stress symptoms and enhances plant growth during water deficit, promoting water deficit avoidance (water-use efficiency) and tolerance (osmoregulation) mechanisms that improve drought resistance. Abstract: Chloride (Cl − ), traditionally considered harmful for agriculture, has recently been defined as a beneficial macronutrient with specific roles that result in more efficient use of water (WUE), nitrogen (NUE), and CO2 in well-watered plants. When supplied in a beneficial range of 1–5 mM, Cl − increases leaf cell size, improves leaf osmoregulation, and reduces water consumption without impairing photosynthetic efficiency, resulting in overall higher WUE. Thus, adequate management of Cl − nutrition arises as a potential strategy to increase the ability of plants to withstand water deficit. To study the relationship between Cl − nutrition and drought resistance, tobacco plants treated with 0.5–5 mM Cl − salts were subjected to sustained water deficit (WD; 60% field capacity) and water deprivation/rehydration treatments, in comparison with plants treated with equivalent concentrations of nitrate, sulfate, and phosphate salts. The results showed that Cl − application reduced stress symptoms and improved plant growth during water deficit. Drought resistance promoted by Cl − nutrition resulted from the simultaneous occurrence of water deficit avoidance and tolerance mechanisms, which improved leaf turgor, water balance, photosynthesis performance, and WUE. Thus, it is proposed that beneficial Cl − levels increase the ability of crops to withstand drought, promoting a more sustainable and resilient agriculture.